Implementasi Akad Ijarah-Asset To Be Leased pada Transaksi Sukuk Ritel di Bank Syariah Mandiri cabang Jombang - Azizuddin, Imam (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Retail sharia bond/sukuk (sharia obligation) becomes investors’ most favorable retail. It is reflected by the high demand of obligation in every implementation of emission accomplished. This research aims to know the implementation of ijara – asset to be leased agreement on the retail sharia bond transaction, and the constraint faced by banks in its implementation. This research uses a descriptive qualitative approach which elaborates the result of observation on the implementation of ijara – asset to be leased agreement on the retail sharia bond transaction. It is then explicated in form of narration and implementation scheme. The instruments are primary data which are collected directly from the informantsand secondary data in form of literatures, product brochures, and previous researches. The result shows that the agreement used by bank in the implementation of Ijarah – Asset to be Leased agreement on the retail sharia bond transaction contains trading agreement (al-bay’) of the underlying asset. The use of wakalah agreement is required when the right to issue sukuk as a representative in the sukuk rental process to the underwriter. On the other hand, a kafalah agreement is required when the right to issue emissions provides guarantees to sukuk management agencies issued. The constraints faced by the bank in the implementation are the fact that the society is still lack of information about sukuk and the customers of retail sharia bond still has incomplete administration data.